ANALISA KEPUASAN PASIEN PADA PELAYANAN DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN DI RUMAH SAKIT DIK PUSDIKKES TAHUN 2022 - Yayah Sya'diah,SST,MKes.; Adika Dwi Prasetyo (APIKES Bhumi Husada Jakarta, 2023)
ABSTRACT Patient satisfaction is the level of patient feelings that arise from the results of the performance of health services obtained after comparing them with what is expected. . The purpose of this study was to describe the level of patient satisfaction with services at the registration of outpatients at the Pusdikkes Education Hospital in 2022. This research is a descriptive quantitative study to get a picture of the level of patient satisfaction at the Dik Pusdikkes Hospital based on 5 dimensions, namely Tangible, Responsiveness, Reliability, Empathy, Assurance. The results of this study showed that patient satisfaction was 84.07%, tangibles was 16.89%, reliability was 16.57%, responsiveness was 16.86%, assurance was 16.79%, and empathy was 16.96%. To overcome this dissatisfaction, officers should improve services such as directing patients after registering because sometimes patients are still confused, officers should explain information in a voice that is not too loud so that patients are not offended, and so on. Keywords: Outpatient., registration, satisfaction level, service.